PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN BERPIKIR KRITIS PADA PEMBELAJARAN DARING DAN LURING - Juniar Alisa; Novan Pratama (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2021)
The problem in this study is the low critical thinking ability of students when learning online which causes student saturation in participating in learning. This study aims to describe students' critical thinking skills from student learning outcomes in economics learning both in conditions of online learning and offline learning in class XI IPA and XI IPS at SMA Negeri 25 Bandung, using the Discussion method. This research is a type of descriptive research. The form of the research is collaborative classroom action research. The sample in this study consisted of 36 students in class XI IPA 1 and 36 students in XI IPS 2. Based on the analysis of the data obtained on student learning outcomes in economics learning by applying the discussion method, students' critical thinking skills increased significantly from cycle I to cycle I. Cycle II at each meeting, the increase was much more significant when learning was carried out offline rather than online learning. This increase can be seen from the results of observations, student test results, field notes, and interviews. The critical thinking ability of students in offline learning when viewed from the test results has increased from 55.6% who achieved the KKM to 83.3% of students who achieved the KKM score, compared to the critical thinking ability of students in online learning which experienced an increase of only 32, 5% to 38.9%. This means that offline learning with the disc method is able to increase critical thinking skills by 27.7%, while online learning is only able to increase critical thinking skills by 6.4%.